The Impact of the 8+8+8 Time Allocation Model on Work Productivity and Quality of Life: A Comparative International Case Study - Suanoom, Cholatis (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This study aims to analyze the impact of the 8+8+8 time allocation model (8 hours each forwork, sleep, and life) on work efficiency and quality of life through a cross-country comparative study. The research employs both quantitative and qualitative methods, including mathematical modelingand it is proven through mathematical processes. The findings indicate that the 8+8+8 time allocation model positively correlates with work efficiency and quality of life in many countries. However, cultural and economic differences affect the model’s implementation. This study presents recommendations for adapting the model to suit each country’s context, aiming to enhance work efficiency and improve the population’s quality of life.